What Schools Are Doing In Developing Science Programs. - Wagner, Guy; Merritt, Eleanor (Education, 1958)
The article focuses on how schools prepare curriculum guides in science for elementary, junior high, and senior high levels in the U.S. These guides have been fruitful sources of ideas which teachers have used for organizing and promoting science programs in their own classrooms. Oftentimes, these curriculum guides have been used to supplement the program delineated by the adopted textbook. It is obvious that the use of several curriculum guides as resource ideas would help local schools determine the content of the science program. There are several reasons why strong science programs should be developed in each local school system throughout the country. Adventure in the realm of science can be fascinating and highly important to children and youth. Teachers then must do their best to develop ways for creative teaching of science.